DECONSTRUCTING MOTHERHOOD IN TANGLED (2010): A DERRIDEAN ANALYSIS OF MOTHER GOTHEL - Hilalliah Isna Putri; Reza Anis Maulidya (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2026)
Film is a visual art form that communicates stories, information, and messages through moving images and sound. It combines various elements such as screenplay, acting, cinematography, directing, music, and editing. Many films also address current social or philosophical themes. A notable example is Tangled (2010), directed by Nathan Greno and Byron Howard and produced by Disney as part of its series of princess films. This journal analyzes the character of Mother Gothel using Jacques Derrida’s post-structuralist approach. It looks at how binary oppositions like mother/monster and freedom/control are called into question. The analysis suggests that Tangled exposes the inherent instability of language, identity, and moral judgment within its narrative framework when deconstructed.